“Epizoonosis of Dermatophytosis”: A Clinico - Mycological Study of Dermatophytic Infections in Central Nepal - Mathur, M; Kedia, SK; Ghimire, RBK (Kathmandu University Medical Journal, 2012)
Background Identification of dermatophytic species in clinical settings are important not only for epidemiological but also for the treatment. Objectives Present study was carried out to find out the clinical variants of Dermatophytosis and species of fungus responsible for the disease. Methods The prospective observational analysis of 200 clinically suspected cases of dermatophytic infection attending Dermatology department of College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan, Nepal. Skin scraping, hair and nail samples were collected and processed according to standard protocol. Results Maximum number of patients enrolled in study were reported for treatment 5-8 weeks after the onset of disease. Overall male predominance was observed and ages between 26-30 years. Tinea corporis was the most common clinical type of tinea with female dominance in our study. 10 % of cases were having extensive Tinea. 71.5% of samples were positive on direct microscopy and 62 % positive on culture. Samples from T capitis were highest positive by direct microscopy (80%) and over all dominant species of fungus isolated in our study was Trichophyton verrucosum (30.6%). Conclusions The study highlighted Tinea corporis as the most common clinical type with female predominance. Overall predominant causative fungal species isolated was Trichophyton verrucosum. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 30-33 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6910